SEBACEOUS CARCINOMA OF GLUTEAL REGION – AN UNUSUAL TUMOUR IN A RARE EXTRAOCULAR SITE - RAVISANKAR PALANIAPPAN; SABARI GIRIEASAN; SUBRAMANIAN KALAIVANI; RAGAVAN HARIPRIYA; PRIYADHARSHINI DURAIRAJU; SELVAKUMAR KOTHANDAPANI (Innovative Journal of Medical and Health Sciences, 2021)
Sebaceous carcinoma is a rare aggressive malignant tumor derived from the adnexal epithelium of sebaceous glands. Sebaceous carcinomas are generally divided as ocular or extraocular locations. Very few cases of extra ocular sebaceous carcinomas have been reported till date. Hereby, we report a 62-year-old female diagnosed with sebaceous carcinoma on the gluteal region with recurrence, and was treated surgically with wide local excision. The extra-ocular site is rare and high degree of suspicion is required and sebaceous carcinoma should be considered as one of the differential diagnosis. KEYWORDS: SEBACEOUS CARCINOMA, GLUTEAL REGION, EXTRAOCULAR SITE